Costs of Dust Collection by Trichodesmium: Effect on Buoyancy and Toxic Metal Release - Wang, Siyuan; Zhang, Futing; Koedooder, Coco; Qafoku, Odeta; Basu, Subhajit; Krisch, Stephan; Visser, Anna‐Neva; Eichner, Meri; Kessler, Nivi; Boiteau, Rene M.; Gledhill, Martha; Shaked, Yeala (Journal of Geophysical Research: Biogeosciences, 2024)
The marine cyanobacterium Trichodesmium has the remarkable ability to interact with and utilize air-borne dust as a nutrient source. However, dust may adversely affect Trichodesmium through buoyancy loss and exposure to toxic metals. Our study explored the effect of desert dust on buoyancy and mortality of natural Red Sea puff-shaped Trichodesmium thiebautii. Sinking velocities and ability of individual colonies to stay afloat with increasing dust loads were studied in sedimentation chambers. Low dust loads of up to ∼400 ng per colony did not impact initial sinking velocity and colonies remained afloat in the chamber. Above this threshold, sinking velocity increased linearly with the colony dust load at a slope matching prediction based on Stoke's law. The potential toxicity of dust was assessed with regards to metal dissolution kinetics, differentiating between rapidly released metals, which may impact surface blooms, and gradually released metals that may impact dust-centering colonies. Incubations with increasing dust concentrations revealed colony death, but the observed lethal dose far exceeded dust concentrations measured in coastal and open ocean systems. Removal of toxic particles as a mechanism to reduce toxicity was explored using SEM-EDX imaging of colonies incubated with Cu-minerals, yet observations did not support this pathway. Combining our current and former experiments, we suggest that in natural settings the nutritional benefits gained by Trichodesmium via dust collection outweigh the risks of buoyancy loss and toxicity. Our data and concepts feed into the growing recognition of the significance of dust for Trichodesmium's ecology and subsequently to ocean productivity.<br